Optimalisasi Komoditas Marongghi dan Ikan Laut Menjadi Produk Olahan Berbasis Kelompok Tani - Soejono, Djoko; Zahrosa, Dimas Bastara; Maharani, Ariq Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2022)
Community Service Program Based on Fostered Village Development, namely utilizing the yard with generative Marongghi/Kelor cultivation. The community in Talango Village has hopes and desires, namely being able to process parts of the marongghi / Moringa plant into food / snack products and by utilizing the potential of fishery resources in Talango Village. The purpose of this community service activity is how to utilize marongghi / Moringa and marine fish commodities into value-added processed products. The method of community service is the activity of socializing the practice of processing marongghi and marine fish, provided assistance for product processing support equipment and assistance for business management of processed products. The results obtained from this activity, among others, motivate the people of Talango Village by trying new things to make samilers combined with marongghi / Moringa plants and marine fish which indeed have very large potential in the Talango area. As well as procurement of equipment grants to increase added value in supporting the processing of maronghi/moringa and marine fish into crackers, samiler, tortilla and stick products